Hubungan Kohesivitas Keluarga dan Internal Locus of Control terhadap Kematangan Karir Siswa Sekolah Menengah Kejuruan - Reni Aprinia Hertanti; Dwi Yuwono Puji Sugiharto (Bulletin of Counseling and Psychotherapy, 2022)
In this study, researchers aimed to find out the relationship of family cohesiveness and internal locus of control with the career maturity of SMKS PGRI Blora students for the 2021/2022 School Year. This type of research is correlational quantitative research. The population in the study is all students of SMKS PGRI Blora class X, XI, and XII in the 2021/2022 school year which amounts to 256 students. The study sample was taken by proportionate stratified random sampling method of 149 students. The instruments used in the study were career maturity inventory, family cohesive scale, and internal locus of control scale. Data analysis techniques use product moment correlation analysis and double correlation. The results of the product moment correlation analysis showed that there was no significant relationship between family cohesiveness and career maturity, while between the internal locus of control and career maturity there was a significant relationship with a moderate correlation value of 0.457, and from the results of the double correlation analysis obtained a significance value of F change = 0.000 or > 0.05, which means there is a significant relationship between family cohesiveness and internal locus of control with the career maturity of students with a score of R = 0.532 that indicate a relationship or correlation between family cohesiveness and internal locus of control with career maturity are categorized as moderate and the contribution or contribution or simultaneous contribution of family cohesiveness variables and internal locus of control with career maturity of 21%, while 79% is influenced by other variables.